Biomechanical analysis of the key element modeling in acrobatic rock-n-roll - Larionova, M. N.; Terekhin, V. S.; Mikhailovskiy, S. P. (Theory and Practice of Physical Culture, 2019)
Background. It is common for the modern acrobatic rock-n-roll community to execute the basic step in different manners/ versions since a standard for execution approved by the athletic and coaching communities is still lacking. The sport specialists tend to set the following requirements to the basic step: efficiency, safety and energy cost efficiency [1, 3, 5]. It should be noted, however, that coaches are still in need of reference points for the training systems - and they may be provided by a basic step model designed on analyses of the movement kinematics with muscular activity harmony/ efficiency profiles to effectively optimize the basic step mastering methods [2, 4, 6]. Objective of the study was to offer a basic step model for the modern acrobatic rock-n-roll based on the movement biomechans analysis. Methods and structure of the study. We used the following research methods: theoretical analysis and summaries of the reference literature; rules of competitions analysis; questionnaire survey of experts (n=62) in acrobatic rock-n-roll; competitive performance (n=180) analyses; and video capture analysis with classification of the basic step execution techniques supported by electromyographic tests. The study data were processed by standard mathematical tools to model an ideal basic step execution and test the model by experiment on a sample of 16 athletes. Results and discussion. Biomechanical test data were used to produce a basic step model as follows: (1) analyze the popular versions of the basic step technique in modern acrobatic rock-n-roll; (2) design a frame basic step model; (3) support it by an efficient modeling algorithm; (4) produce a basic step model; (5) test the model by an experiment; (6) process and analyze the experimental test data; and (7) analyze benefits of the basic step model for the modern acrobatic rock-n-roll. Components of the biomechanical model at the primary modeling stage were shaped up on the assumption that the model is designed to mimic the target movement sequence; and that the right body side (lead leg side) biomechanics and the upper limbs movement sequences are virtually the same (having insignificant differences) for the basic step versions. This was the reason for the modeling process giving a special priority to the left (swing leg) side biomechanics. Furthermore, we estimated contribution of every basic step element to rank the elements in the following hierarchy/ sequence for the modeling algorithm: see Figure 1.